Errors in the Use of English Tenses - Garrido, Carmen Gloria; Rosado Romero, Cristina de la Luz (Íkala, Revista de Lenguaje y Cultura, 2012)
This article presents the results of an error analysis investigation carried out in Concepción, Chile, with a group of forty-eight native speakers of Spanish studying to become EFL teachers at Universidad San Sebastián. All participants were first year students who had studied English tenses and aspects for a year. The objectives of this investigation were the identification of students' errors regarding the use of tenses and aspects in English, the design of a hierarchy of difficulty and the explanation of main errors. According to the results obtained, after a year of formal instruction, students still showed problems with the correct use of English tenses and aspects. The main problem was accurately matching tenses and aspects to different contexts. Findings provide useful information to design remedial programmes to help students become successful in the use of English tenses and aspects.